“DESTITUCIÓN DE LAS AUTORIDADES DE ELECCIÓN POPULAR AL NO CUMPLIR CON SUS PROPUESTAS DE TRABAJO - Freire Muicela, Bryan David (2021)
The present investigation that is presented under the form of thesis refers to a legal problem that deserves to be transformed to solve and overcome the socio-legal problem that is identified in Article 48 of the Organic Law of the General Comptroller of the State in which it is establish the execution and imposition of sanctions to which public servants are subjected, what is not established and has come to be considered necessary is the implementation of a sanction for those people who come to power and do not comply with their work proposals Promises made in the campaign that serve to gain popularity, so a direct sanction by the control bodies that the current legal system has would be the ideal, for the people it would be a very powerful weapon to have this sanction when there is omission in the functions and duties of the popular election authorities, this proposal encompasses two great things, sanctioning the failure itself or their proposals and a control regarding compliance with them, this for all those authorities of popular election in the event that they do not comply with their proposals, they will be sanctioned with the dismissal of the function for which they were elected and that they are prohibits them from holding a popularly elected post for life